2022
DOI: 10.1002/pon.5886
|View full text |Cite
|
Sign up to set email alerts
|

How does the Untire app alleviate cancer‐related fatigue? A longitudinal mediation analysis

Abstract: Objective A waiting‐list randomized controlled trial supported the effectiveness of the multimodal Untire app in reducing cancer‐related fatigue (CRF) in cancer patients and survivors. However, little is known about the causal mechanisms of different app components through which the intervention effect was achieved. We aim to examine whether specifically targeted factors (i.e., fatigue catastrophizing, depression, mindfulness, sleep, and physical activity) mediated the intervention effects of the Untire app on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Most studies have reported results for respondents from specific age groups, such as adolescents and young adults [5,16,39] and older individuals [19,37]. Yet, few scholars have reported comparative responses of intervention users from different age groups [7,14,15,78,90].…”
Section: Theme 3: Methodological Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies have reported results for respondents from specific age groups, such as adolescents and young adults [5,16,39] and older individuals [19,37]. Yet, few scholars have reported comparative responses of intervention users from different age groups [7,14,15,78,90].…”
Section: Theme 3: Methodological Approachmentioning
confidence: 99%
“…text messages [16,23,74], wearable devices [29,83], and mobile apps [14,27,41,84,85], as forms of delivery. Recent studies have also begun to integrate mHealth interventions with gamification [72,86] and other smartphone features like location sensing [87], thereby providing deeper insights into how these interventions influence participants.…”
Section: For Example Mhealth Interventions For Cancer Have Predominan...mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this limitation, most mHealth apps in research settings provide human support at varying levels-from high support through guided interventions (ie, involving guidance from a trained professional, eg, through live videoconferencing or web-based workshops) to lower levels of support through study processes (eg, screening visits or telephone surveys conducted by the study team). In the rare studies available on unguided cancer-related mHealth apps with no human support [68][69][70], engagement rates were <50%. One reason could be that existing researcher-developed apps are not engaging enough and, therefore, need human support to motivate participants [18,71].…”
Section: Comparison With Prior Workmentioning
confidence: 98%
“…Furthermore, mindfulness-based clinical interventions and yoga appear to be feasible interventions, and beneficial effects have been reported on several physical and psychosocial symptoms in patients with cancer, such as patients' psychosocial adjustment to their disease and improvement of biomarkers of stress, inflammation, and immune function [35][36][37]. Encouraging physical exercise, psychoeducation, mindfulness-based interventions, and yoga have therefore been included in web-based programs and eHealth apps targeting CRF, with promising results [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%